Structural fatigue crack growth on a representative volume element under cyclic strain behavior. (May 2015) - Shi, K.K.; Cai, L.X.; Bao, C.; Wu, S.C.; Chen, L.
Highlights: A unified cyclic stress and strain field is formulated by using λ and ω . FCG models are developed by PSE and LDA failure criteria, respectively. SFCG model is proposed from failure life and non-self-similar crack shape law. Good agreement between prediction results and experimental results is found. Abstract: By introducing parameters λ and ω into the crack tip field, a unified cyclic stress and strain field was first formulated by using the Hutchinson-Rice-Rosengren (HRR) field and the Rice-Kujawski-Ellyin (RKE) field under plane stress states in the present study. On the basis of the plastic strain energy and the linear damage accumulation, two fatigue crack growth models without any artificial parameters were then proposed from a representative volume element of cyclic strain behavior. The fatigue crack growth model included parameters λ and ω which showed the effect of two singularity fields. In addition, a simplified structural fatigue crack growth model was eventually established in terms of the fatigue life of each point on the crack front and the non-self-similar shape evolution law. Finally, the predictions of models are compared with the experimental data and the agreement is found to be fairly good.